Intercultural Project Leadership: Observations on the Finnish-Swedish Interreg Project Cultural Arena Kvarken - Ehrs, Susanna (My University, 2004)
In today’s world cross-border cooperation is becoming increasingly more common. One important aspect of the European Union’s regional policy today is cooperation between regions in different member countries, in order to improve and strengthen the cross-border unity. But seeking partners outside the national borders also causes difficulties, since going across a national border means having to encounter a new culture and a different way of thinking, living and acting. The subject of this study is intercultural project leadership. Project leadership in itself is a field with special challenges, since working in a project setting differs from working in a traditional organisation. A project leader often has a high level of responsibility but a lower level of authority than a traditional manager. When further adding the dimension of different cultures, it signifies an increased demand for good communication skills and human resource skills for the project leader, in order to accomplish the best possible performance from all members of the project. The aim of this study is to examine and compare leadership, communication and cultural differences within an inter-cultural project situation between Finland and Sweden. I wanted to investigate how it is to have a managerial role in a project that takes place in two countries simultaneously; the challenges, special preconditions, main problems and opportunities of such a venture. The composition of this study is threefold. Firstly, to find out if there are differences between Finnish and Swedish leadership and organisational behaviour. Secondly, to learn how the communication process flows in an intercultural working environment. And thirdly, to investigate if there are cultural differences between Finland and Sweden, with a special focus on organisational culture. The case for this study is Interreg IIIA project Cultural Arena Kvarken, with the aim of establishing a cultural cooperation between the regions of Västerbotten in Sweden and Österbotten in Finland. The material for the theoretical part of this study was obtained by examining relevant literature in the fields of leadership, communication and culture, with a special focus on the works by Chester Barnard and Geert Hofstede. The empirical material is a result of interviews with 16 project leaders within the project Cultural Arena Kvarken. Although Finland and Sweden are geographically close, there are many differences in between the two countries. The Finns and the Swedes have differing views on substantial matters such as democracy versus hierarchy, importance of discussion and reaching of consensus, role of authorities, differing communication behaviour etcetera. The leadership style within an intercultural project needs to be adapted to the prevalent circumstances. The same type of behaviour that functions in a one-nation setting is not necessarily appropriate in an intercultural situation. To have knowledge of different cultures, to come prepared and open-minded, are all good qualifications for a functioning cooperation. And the most important factor for a good cooperation between countries is the willingness of the participants to work towards the same goal, and not be hindered by differences.
Keywords: Projects; project leadership; culture; communication; fi=Hallintotiede : European Civil Servants - kansainvälisen hallinnon ohjelma|